1995
DOI: 10.1007/bf00212495
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants in fishes from great lakes-influenced sections and above dams of three Michigan Rivers: III. Implications for health of bald eagles

Abstract: Recently, there have been discussions of the relative merits of passage of fishes around hydroelectric dams on three rivers (Au Sable, Manistee, and Muskegon) in Michigan. A hazard assessment was conducted to determine the potential for adverse effects on bald eagles that could consume such fishes from above and below dams on the three primary rivers. The hazard assessments were verified by comparing the reproductive productivities of eagles nesting in areas where they ate primarily fish from either above or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 50 publications
3
52
0
Order By: Relevance
“…The calculated BMFs of p,p 0 -DDE in osprey eggs (47) and eagle eggs (47) were similar to the calculated BMF for the herring gull (55; Norstrom et al, 2007). These calculated BMFs were between field-estimated BMFs of 22 for bald eagle (Giesy et al, 1995) and 87 for osprey (Henny et al, 2003). Field-estimated BMFs of slowly excreted contaminants such as p,p 0 -DDE are subjected to considerable error because it is impossible to accurately estimate the true exposure of the bird that results in the egg residues.…”
Section: Screening Level Risk Evaluationsupporting
confidence: 59%
See 1 more Smart Citation
“…The calculated BMFs of p,p 0 -DDE in osprey eggs (47) and eagle eggs (47) were similar to the calculated BMF for the herring gull (55; Norstrom et al, 2007). These calculated BMFs were between field-estimated BMFs of 22 for bald eagle (Giesy et al, 1995) and 87 for osprey (Henny et al, 2003). Field-estimated BMFs of slowly excreted contaminants such as p,p 0 -DDE are subjected to considerable error because it is impossible to accurately estimate the true exposure of the bird that results in the egg residues.…”
Section: Screening Level Risk Evaluationsupporting
confidence: 59%
“…Field-estimated BMFs are available for bald eagle and osprey (e.g. Giesy et al, 1995;Henny et al, 2003), but we derived the DECs for p,p 0 -DDE using calculated BMFs to more accurately predict concentrations that pose a risk to bald eagle and osprey. Specifically, a bioaccumulation model for lipophilic contaminants that predicts the BMF of p,p 0 -DDE in herring gull (Larus argentatus) eggs was used to estimate BMFs in bald eagle and osprey eggs (Norstrom et al, 2007).…”
Section: Screening Level Risk Evaluationmentioning
confidence: 99%
“…Concentrations of TCDD-EQ at reference sites in previous studies ranged from below detection to 6 pg/g (Giesy et al, 1995;van den Heuvel et al, 1996;Schmitt et al, 2002;Whyte et al, 2004), and 6 pg/g has been suggested as a threshold for toxicity to fish-eating wildlife (Giesy et al, 1995). This threshold was attained by one bass sample from Station 512 (Table 6).…”
Section: Exposure Indicatorsmentioning
confidence: 88%
“…Studies have used the H4IIE bioassay to identify areas where fish have accumulated high concentrations of TCDD-EQs relative to fish from reference locations. These regional comparisons have revealed PHH contamination in fish from industrial regions of the Great Lakes Giesy et al, 1995;Tillitt et al, 1996) and in fish inhabiting areas near pulp and paper mill effluents (van den Heuvel et al, 1996;Whyte et al, 1998). In one of the few studies that report TCDD-EQs in aquatic invertebrates, McDonald et al (1994) and Kennicutt et al (1995) reported 10-fold greater TCDD-EQs in clams from the heavily PCB-contaminated Winter Quarters Bay, Antarctica, as compared to clams collected from a uncontaminated reference location (Table 11).…”
Section: B H4iie Toxic Equivalents (Tcdd-eqs) In Field Studies and Bmentioning
confidence: 99%
“…A value of 1 would indicate that a population is just at the threshold for adverse effects and values greater than 1 would indicate a probability that adverse effects could occur. Giesy et al (1995) measured TCDDEQs, organochlorine insecticides, PCBs, and mercury in composite samples from eight different fish species that serve as prey for bald eagles (Haliaeetus leucocephalus). These fish were collected above and below hydroelectric dams on three Michigan rivers, with fish residing below the dams having access to the Great Lakes.…”
Section: H4iie-derived Tcdd-eqs As a Tool For Hazard Assessmentmentioning
confidence: 99%